2022
DOI: 10.3390/mi14010053
|View full text |Cite
|
Sign up to set email alerts
|

A Framework to Predict Gastric Cancer Based on Tongue Features and Deep Learning

Abstract: Gastric cancer has become a global health issue, severely disrupting daily life. Early detection in gastric cancer patients and immediate treatment contribute significantly to the protection of human health. However, routine gastric cancer examinations carry the risk of complications and are time-consuming. We proposed a framework to predict gastric cancer non-invasively and conveniently. A total of 703 tongue images were acquired using a bespoke tongue image capture instrument, then a dataset containing subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…According to the principles of TCM, tongue manifestation serves as a crucial indication of "collaterals" [30]. It plays a significant role in various disorders such as gastric diseases [21], rheumatic conditions [31], hepatic disorders [32], and tumors [10], among others. Tongue color, thickness, moisture, and other changes, as well as the rich network of vessels in the tongue area [30], to a certain extent, can reflect the pathological changes in the spleen, stomach, internal organs, joints, and many other parts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the principles of TCM, tongue manifestation serves as a crucial indication of "collaterals" [30]. It plays a significant role in various disorders such as gastric diseases [21], rheumatic conditions [31], hepatic disorders [32], and tumors [10], among others. Tongue color, thickness, moisture, and other changes, as well as the rich network of vessels in the tongue area [30], to a certain extent, can reflect the pathological changes in the spleen, stomach, internal organs, joints, and many other parts.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have indicated that non-invasive features, including imaging characteristics and clinical phenotypic information, have the potential to predict the occurrence and progression of PLGC. The theory of Traditional Chinese medicine (TCM) suggests that the tongue’s shape, color, size, and coating characteristics detected using tongue images reflect health status and disease severity/progression, and recent studies have shown the potential for tongue surface and color characteristics to assist in the diagnosis of PLGC [9, 10]. For digestive diseases, tongue images characteristics have been found to correlate with gastroscopic observations and predict gastric mucosal health [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al 5 studied the tongue diagnosis indices for gastroesophageal reflux disease (GERD), and they used an automatic tongue diagnosis system (ATDS) to extract the tongue indices and found that the saliva amount ( p = .009) and thickness of the tongue's fur ( p = .036), especially that in the spleen–stomach area (%) ( p = .029), were significantly greater in patients with GERD. Handcraft features of tongue images from physicians were weighted and filtered by the XGBT algorithm in research, 86 and the EfficientNet network was used to classify gastric cancer based on the selected features. Meng et al 87 used tongue image high-level features extracted from a CNN framework to diagnose gastritis and found that the deep learning framework extracted more suitable features than histogram of oriented gradients (HOG), local binary pattern (LBP), and scale-invariant feature transform (SIFT), which extract the handcrafted low-level features.…”
Section: Tongue Image For Disease Diagnosismentioning
confidence: 99%
“…For example, recent studies have indicated that tongue image characteristics show correlations with gastroscopic observations and could be used to predict gastric mucosal health [ 21 , 22 ]. In addition, it was revealed that tongue surface and color characteristics could be used as indicators to assist in gastric cancer diagnosis [ 23 , 24 ]. Moreover, morphological markers based on tongue images are considered to be valuable for risk screening for other diseases, such as diabetes, fatty liver disease, and COVID-19 [ 17 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%